2014
DOI: 10.1145/2602571
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Aware Cloud Bursting for Enterprise Applications

Abstract: The high cost of provisioning resources to meet peak application demands has led to the widespread adoption of pay-as-you-go cloud computing services to handle workload fluctuations. Some enterprises with existing IT infrastructure employ a hybrid cloud model where the enterprise uses its own private resources for the majority of its computing, but then “bursts” into the cloud when local resources are insufficient. However, current commercial tools rely heavily on the system administrator’s knowledge to answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 26 publications
2
62
0
3
Order By: Relevance
“…The output of their research indicated the need to research on the solutions for various optimization problems associated with the hybrid SaaS concept. Subsequently, related works such as [16] and [17] focused on the design of cost efficient VM migration algorithms which enables the scale up of local data center resources to the public Cloud in the context of Cloud bursting. However, their works considers workload characteristics as static.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The output of their research indicated the need to research on the solutions for various optimization problems associated with the hybrid SaaS concept. Subsequently, related works such as [16] and [17] focused on the design of cost efficient VM migration algorithms which enables the scale up of local data center resources to the public Cloud in the context of Cloud bursting. However, their works considers workload characteristics as static.…”
Section: Related Workmentioning
confidence: 99%
“…As indicated in (steps [25][26][27][28][29][30], for each job found in W, the algorithm will first search for other VMs in the private Cloud which may be free and satisfies P1 to complete the job. Otherwise, the VM instance in the public Cloud which satisfies P2 will be rented On-demand to run the job (steps [16][17][18]. The solution of P2 is is simply the minimum resulting value that is yielded when the price of each VM rented from the public Cloud is multiplied by the runtime estimate α k of the k th job.…”
Section: B Provisioning Policies 1) Private Provisioning Policymentioning
confidence: 99%
“…Seagull [6] et al provide a framework for cloud bursting that efficiently precopies and migrates applications to a public cloud when local infrastructure becomes overloaded. This solution enables performing agile provisioning of resources across private and public clouds.…”
Section: Related Workmentioning
confidence: 99%
“…To address this issue, hybrid cloud bursting [48] (complement on-premise virtual machines with temporary off-premise virtual machines) has seen a rapid increase in popularity among big data analytics users.…”
Section: Discussionmentioning
confidence: 99%